SCALP ACUPUNCTURE SEBAGAI TERAPI LAGOPHTHALMOS PADA BELL’S PALSY KRONIK: USING SCALP ACUPUNCTURE FOR TREATING LAGOPHTHALMOS IN CHRONIC BELL’S PALSY - Eric Hartono; Budi Oetomo (Jurnal Sinaps, 2018)
Latar Belakang: Scalp acupuncture sering digunakan dalam rehabilitasi paralisis karena stroke, multiple sclerosis, bell palsy, kecelakaan mobil, dan penyakit Parkinson. Laporan Kasus: Laki-laki 54 tahun datang dengan keluhan utama wajah sisi kanan kesemutan dan terasa lemah secara progresif sejak 1 bulan yang pertama kali dirasakan saat bagun tidur wajah sebelah kanan seperti turun dan tidak dapat menutup mata kanannya. Diskusi: Dalam teori TCM, Bell's palsy dikaitkan dengan blok- blok aliran chi pada meridian Yang Ming dan Shao Yang. Gejala yang terkait dengan sindrom ini termasuk kelemahan otot-otot wajah dan mengarah ke gejala khas Bell's palsy. Perawatan dilakukan dengan tusukan titik-titik spesifik dalam meridian ini untuk mengembalikan aliran chi, yang idealnya meningkatkan pemulihan dari kondisi. Kesimpulan: Laporan ini menyajikan kasus seorang pria berusia 54 tahun dengan gejala sisa kronis dari Bell's palsy yang melaporkan hasil yang baik setelah perawatan chiropraktik, olahraga, dan akupunktur gabungan. Kata kunci: Bell’s Palsy, Erosi Kornea, Lagophthalmos, Akupunktur ABSTRACT Background: Scalp acupuncture areas are frequently used in the rehabilitation of paralysis due to stroke, multiple sclerosis, bell’s palsy, automobile accident, and Parkinson's disease. Case Report: A 54th-years-old man complaining of right-sided facial numbness and weakness progressively for 1 month. He reawakened in the morning to right-sided facial droop, inability to close right eye and numbness to the right side of his face. Discussion: In TCM theory Bell’s palsy is associated with blocks to the flow of chi of the Yang Ming and Shao Yang meridians, which cause a syndrome labeled Wind-Phlegm. Symptoms associated with this syndrome include weakness of the facial muscles and lead to the characteristic symptoms of Bell’s palsy. Treatment is accomplished by the needling of specific points in these meridians to restore the flow of chi, which ideally enhances recovery from the condition . Conclussion: This report presents the case of a 54 year-old male with chronic sequelae from Bell’s palsy who reported good results after combined chiropractic, exercise and acupuncture treatments. Keywords: Bell’s Palsy, Corneal Erosion, Lagophthalmos, Scalp Acupuncture